Mangroves of Maharashtra State (India): Diversity and Sustainability - Kulkarni, N A; Bhosale, L J (Plantae Scientia, 2021)
Mangroves are defined as tropical and sub-tropical forests with a diverse floristic composition bordering the sea on muddy or peaty low lands periodically submerged or influenced by the tides. Maharashtra is one of the coastal states of India, with many rivers emerging from Sahyadri ranges and meeting the Arabian Sea. The coast line available for Maharashtra state is 720 km. Ratnagiri, Sindhudurg, Raigad, Thane and Mumbai are the five coastal districts of the state of Maharashtra. All the districts together have more than 55 small, medium and large estuaries. It is found that estuaries like Vijaydurg shows maximum mangrove area of and estuaries like Kelye shows minimum area. It also reveals that the species like E. agallocha, A. ilicifolius, R. mucronata, A. officinalis and A. marina show maximum percentage of occurrence as compared to the species like X. granatum, C. iripa, B. cylindrica, S. caseolaris, H.fomes and T. gallica. The studies on mangrove biodiversity in five districts show the major variations. The study found 20 typical mangroves, 10 halophytic species, 13 border line mangroves and 15 mangrove associates from all these districts. Among these the uncommon and threatened greet pied Hornbill (Buceros bicornis) have been found at some sites. Some of the common crab species are Uca roseus, Uca lactea annulipes and Uca vocans. The species like Scylla serrata and Portunus pelagius are edible. In the present study 13 sp. of Molluscs, 25 species of edible fish, 9 species of Reptilia, 45 sp. of birds and 10 species of Mammalia are found. It is found that out of twenty-four species analyzed, some species are analyzed as Critically Endangered (CR), some are found Endangered (EN). From this study it is found that all sites being under human pressure the natural zonation pattern is not seen. The existing zonation pattern is a result of natural distribution and human disturbances.